Dossier: Pluri-Culture and Migrant Writings/ Pluri-Culture et Écrits Migratoires - Sabiston, Elizabeth (Revue CMC Review, 2015)
The dossier focuses on the publication and reception of Pluri-Culture and Migrant Writings/ Pluri-Culture et écrits migratoires (Sudbury: Human Sciences Monograph Series, 2014), the Proceedings of the May 2012 International Conference held at York University and organized by the CMC. The bilingual, interdisciplinary collection of thirty-three essays was edited by Elizabeth Sabiston and Robert J. Drummond, and supported by SSHRC/CRSH. The dossier includes an account of the book launch, as well as book reviews, critical comments, and other related material.